A Comparative Study of the Heavy Metals in the Meat of Chickens in Different Cities of Pakistan. A Review - Abdul Hakeem; Khan, Naqeebullah; Attiq-ur-Rehman; Khan, Samiullah (Al-Nahrain Journal of Science, 2020)
The quality of food stuff is the main concern of everyone and scientific community is busy in monitoring and ensuring the quality. The aim of this review is study the importance of heavy metals in and the concentrations of these in the meat of chickens. The data of heavy metals concentration (Pb, Cd, Zn, Cu, Ni) in chicken meat determined in various cities of Pakistan such as Karachi, Kohat, Lahore and Kasur city is presented in this review and a comparison study is conducted among the results. The mean accumulation of lead was observed the highest in the research study performed in Lahore of four cities of Pakistan due to the lead contaminated chicken food while that of Karachi was observed the lowest mean level of Pb of all. Kohat was found second to all. The mean concentration of cadmium was observed the highest level in Kohat, because the main source of cadmium is food, among all concerned cities of Pakistan. The research study in Karachi was observed the lowest amount of cadmium in liver. However, no any significant difference of Cd in liver between Lahore and Kasur was observed. The mean concentration of Zn was observed the highest in the liver of Lahore as source of the metals are chicken food than other studies compared. The mean levels of zinc in study of Karachi were observed the lowest of all. On the other hand, the mean accumulation of nickel was observed highest in Karachi due to the industrial wastes that contaminate the chicken food, among the already performed studies of all three cities while Kohat study result was observed the lowest mean concentration of nickel among the three.